FISHBURN'S METHOD: A METHOD OF DRUGS CLINICAL EFFICIENCY EVALUATION (ON THE EXAMPLE OF ANTIBIOTICS, APPLIED FOR THE TREATMENT OF ACUTE AND RECIDIVOUS OBSTRUCTIVE BRONCHITIS OF CHILDREN) - O. V. Zhukova; T. M. Konyshkina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have studied a structure of a therapy with antibiotics which is applied for patients with acute and recidivous obstructive bronchitis. We have determined a clinical efficiency of each antibiotic used. We have presented a methodology of weight coefficients calculation efficiency by the Fishburn's method. We have also presented a method for antibiotics distribution by the levels of clinical efficiency - high, medium, and low.